A common place is not my place: artistic relations between Mexico and the United States in a globalised world - Montero Fayad, Daniel (Re-visiones, 2024)
The positioning of Mexico as a country of transit, since the end of the 1980s, particularly in relation to the United States, allows us to take into account its geopolitical condition as a place of global delocalisation and relocalisation. At the same time, we can therefore consider the effects of this situation on both countries. In this condition of transit, the narrative possibilities of a historical discourse both to and from Mexico and the United States have changed considerably, modifying thus the ways of understanding artistic production. In this sense, we must understand the correlations not as an inside and an outside, but rather in terms of flow and porosity. This article shows how narratives and practices within contemporary Mexican art have changed based on the bilateral relations with the Unites States, and it also elaborates on some particular cases in which local artistic production has transformed in the last 20 years due to the flows relative to the Mexican territory.